2015
DOI: 10.18606/2318-1419/amazonia.sci.health.v3n3p17-25
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Ultrassom Focalizado (HIFU) no Tecido Adiposo Abdominal

Abstract: Introdução: O contorno corporal preocupa muitas mulheres e o ultrassom focalizado (HIFU) atua no tecido adiposo reduzindo-o. Objetivo: Comparar os efeitos do ultrassom focalizado sobre o tecido adiposo abdominal de mulheres praticantes e não praticantes de atividade física. Materiais e Métodos: A amostra foi composta por 22 mulheres voluntárias com sobrepeso, divididas igualmente em dois grupos (G1não praticantes de atividade física e G2 praticantes), e subdivididas de acordo com a faixa etária em A de 20-29 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…A study by Brito et al 7 , with a population of 22 female volunteers, aged 20 to 39 years, amongst which some did and some did not practice physical activities, showed a significant reduction in the lipid profile in the values of total cholesterol and LDL in the group of individuals who practiced physical activities after the use of the ultrasound cavitator in abdominal adipose tissue. It is worth mentioning that repeated applications with the UCV device in a period inferior to 96 hours, according to this research, could bring risk of hepatic steatosis if the patient did not undergo excessive metabolic expenditure.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study by Brito et al 7 , with a population of 22 female volunteers, aged 20 to 39 years, amongst which some did and some did not practice physical activities, showed a significant reduction in the lipid profile in the values of total cholesterol and LDL in the group of individuals who practiced physical activities after the use of the ultrasound cavitator in abdominal adipose tissue. It is worth mentioning that repeated applications with the UCV device in a period inferior to 96 hours, according to this research, could bring risk of hepatic steatosis if the patient did not undergo excessive metabolic expenditure.…”
Section: ■ Discussionmentioning
confidence: 98%
“…Such degradation products are safely transferred through the blood. Moreno et al 5 reported that triglyceride levels may rise within normal levels in the first 48 h after application of the focused ultrasound device, demonstrating that the equipment operates under a safe technique procedure 7,8 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Thus, the search for unconventional alternatives, such as technologies that help to find this result, grows (BRITO, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Entre os tratamentos estéticos conservadores pode se destacar a praticidade no uso de ultrassom focalizados de alta potência e alta intensidade (HIFU) e eletrolipólise, agindo diretamente no tecido adiposo, causando ruptura das células de gordura, onde os triglicerídeos dispersam-se no espaço intersticial sendo transportado pelo sistema linfático até o fígado [4][5][6].…”
Section: Introductionunclassified